PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN METODE PRAKTIKUM DAN WINDOW SHOPPING DALAM PEMBELAJARAN KIMIA - Ariani Prihartanti; Eny Winaryati; Dian Wulandari (LitbangMu Jawa Tengah and Teacher Professional Education UNIMUS, 2023)
This research was conducted using qualitative research, classroom action research. This research took subjects at SMA Negeri 1 Sumber for the 2023/2024 academic year. This research applies learning using the PBL model with practical methods and window shopping on factors that influence reaction rates. The results of using this method are very effective in increasing student motivation which has an impact on increasing student learning outcomes. This is supported by the changes obtained during learning, namely making students enthusiastic and cheerful in learning chemistry, and appearing interactive and active in participating in learning. Based on attitude assessment observations, the results showed that 65% of students were very good and 35% of students were good. Based on observations of skills assessment in practicum, 100% of students were very good. Based on observations of presentation skills assessment, 35% of students are very good and 65% of students are good. Based on the learning evaluation, it was found that 5% of students had not fulfilled the KKTP and 95% had fulfilled the KKTP with an average score of 92. This shows that PBL learning is able to improve student learning outcomes so that it can be an alternative learning for chemistry teachers.